Potent long-term cardioprotective effects of single low-dose insulin-like growth factor-1 treatment postmyocardial infarction - O'Sullivan, J.; Leblond, A.; Kelly, G.; Kumar, A.; Metharom, Pat; Büneker, C.; Alizadeh-Vikali, N.; Hristova, I.; Hynes, B.; O'Connor, R.; Caplice, N. (2011)
Background-Insulin-like growth factor-1 (IGF-1) is recognized as an important regulator of cardiac structure and cardiomyocyte homeostasis. The prosurvival and antiapoptotic effects of IGF-1 have been investigated in vitro and in rodent models of myocardial infarction (MI). However, the clinical application of IGF-1 has been hampered by dose-dependent side effects both acutely and during chronic administration. We hypothesized that single, low-dose IGF-1 (LD-IGF-1) administered locally and early in the reperfusion phase after acute MI in a large animal model would avoid significant side effects but would have prosurvival effects that would manifest in long-term structural and functional improvement after MI treatment. Methods and Results-Forty-four female Landrace pigs underwent intracoronary administration of LD-IGF-1 or saline 2 hours into the reperfusion phase of acute left anterior descending artery occlusion MI. In the area of infarction, IGF-1 receptor and signaling responses were activated at 30 minutes and cardiomyocyte cell death attenuated at 24 hours after LD-IGF-1 but not saline treatment. Hemodynamic and structural studies using pressure-volume loop, CT, and triphenyltetrazolium chloride analysis 2 months post-MI confirmed a marked reduction in infarct size, attenuation of wall thinning, and augmentation of wall motion in the LD-IGF-1-treated but not in the saline-treated animals. These regional structural benefits were associated with global reductions in left ventricular volumes and significant improvement in left ventricular systolic and diastolic function. Conclusions-One-time LD-IGF-1 effects potent acute myocardial salvage in a preclinical model of left anterior descending artery occlusive MI, extending to long-term benefits in MI size, wall structure, and function and underscoring its potential as an adjunctive therapeutic agent. © 2011 American Heart Association, Inc.